The pysat ecosystem - Stoneback, R. A.; Burrell, A. G.; Klenzing, J.; Smith, J. (Frontiers in Astronomy and Space Sciences, 2023)
The Python Satellite Data Analysis Toolkit (pysat) is an open source package that implements a general data analysis workflow for arbitrary data sets, providing a consistent manner for obtaining, managing, analysing, and processing data, including modelled and observational ground and space-based data sets for the space sciences. Pysat enables systematic and individual treatment of data as well as simplifies rigorous data access and use, allowing larger-scale scientific efforts including machine learning, data assimilation, and constellation instrumentation processing. Since the start of its development pysat has evolved into an ecosystem, separating general file and data handling functionality from both individual data set support and generalized data analysis. This design choice ensures that the core pysat package has only the necessary functionality required to provide data management services for the wider development community. The shift of data and analysis support to ecosystem packages makes it easier for the community to contribute to, as well as use, the full array of features and data sources enabled by pysat. Pysat's ease of use, and generality, supports adoption outside of professional science to include industry, citizen science, and education.